The automated cell counter for the analysis of morphological characteristics and the quantitative estimation of starch granules in different potato varieties - D. I. Volkov; O. A. Sobko; P. V. Fisenko; N. V. Matsishina; A. A. Gisyuk; I. V. Kim; M. A. Ermak (Овощи России)
Relevance. Potato starch is widely used in the food, textile, perfume and pharmaceutical industries. The starch content and the size of starch granules in potato tubers are varietal characteristics (Solanum tuberosum L.). The knowledge of morphological properties of starch plays a key role in the technologies for the production of consumer and industrial goods.Materials and methods. The studies were carried out in 2020-2021 at the experimental base of Federal State Budget Scientific Institution “Federal Scientific Center of Agricultural Bio-technology of the Far East named after A.K. Chaiki” (Primorsky Krai). The object of the research were 11 varieties of different maturity dates. Morphological structure of starch granules was evaluated by image analysis on Countess II FL automated cell counter.Results. The varieties studied had predominantly rounded and oval pellets regardless of maturity and genetic origin. Differences in starch granule size depending on tuber size and ripeness group were noted. Early maturing varieties had granule size less than 20 microns regardless of tuber fraction. The exception is the variety Queen Anne, in small tubers of this variety starch granules larger than 20 microns is 67.86%. It was noted that the proportion of medium and large grains increased in varieties with a longer growing season. For example, the variety Augustin medium-ripening had a proportion of medium and large grains in the large and small tuber of 47.72 and 41.48%, respectively. The maximum number of grains larger than 20 microns was observed in the mid-late varieties Kazachok (63.77%) and Smak (92.22%).Conclusion. The method using a cell counter and subsequent processing of microphotographs of starch granules is an accessible, economical, simple and effective approach to phenotyping potato varieties and hybrids of Solanum tuberosum L. by physical and chemical parameters of starch. This method can be used for accelerated analysis of a large number of samples on a limited amount of natural material, including in field and farm laboratories.